Haiti--Let's Talk Competition A Brief Review of Market Conditions - Pop, Georgiana (The World Bank, 2016)
This report presents an analysis of competition conditions and market concentration in Haiti. Based on available import data and available information on economic group connections, it also presents a limited analysis of the economic groups and companies that operate in Haiti, with a focus on highly concentrated markets. This analysis found that Haitian markets are constrained by a mix of factors, including operational business risks related to weak competitive conditions; highly concentrated markets which likely result in higher consumer prices; and a concentration of ownership in the most powerful firms, which seem to benefit from preferential treatment such as reduced customs duties